Design, Play, Procure : Unleashing Gamification’s Potential To Reshape The Interior Design Business Model And Facilitate Direct Interior Furnishing Procurement - Saputra, Augustine Sally; Rustiadi, Sonny (Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This mixed methods research explored user perceptions and engagement dynamics surrounding a proposed gamification concept for interior design and interior furnishing procurement. A multi-phase approach combining exploratory qualitative and quantitative methods with Technology Acceptance Model (TAM), Theory of Planned Behaviour (TPB) and Value Co-Creation (VCC) constructs. Thematic analysis from exploratory qualitative interviews revealed perceived benefits around enhanced collaboration, customization, and engagement, with expectations for effortless spatial visualization and creative experimentation. However, adoption outlook varied across age groups. Exploratory quantitative analysis using PLS-SEM showed perceived usefulness and social influences driving favorable attitudes, while confirmatory quantitative analysis with MRL constructs using CFA and PLS-SEM demonstrated positive early experiences markedly influencing eventual user advocacy. Key Recommendations center on agile, human-centric implementation focused on participative value creation for sustained relevance. Blended physical-digital strategies addressing category-specific barriers are advised, alongside participative value co-creation sustaining designer and client creativity amid digitization. While findings provide measured optimism given strong receptivity and adoption readiness metrics, targeted transition sequencing grounded in user realities, not technical proficiency alone, is imperative for contextually synchronized platform assimilation. Through meticulous multi-method inquiry, this pragmatic research elucidates requisite considerations around human-centric innovation for sustainable industry evolution.